Controlled Microstructuring of Janus Particles Based on a Multifunctional Poly(ethylene glycol). Issue 19 (28th August 2013) - Sokolovskaya, Ekaterina; Yoon, Jaewon; Misra, Asish C.; Bräse, Stefan; Lahann, Jörg
<x xml:space="preserve">Abstract</x> A novel water insoluble, multifunctional poly(ethylene glycol), poly(hydrazide ethylene glycol‐co‐benzyl glycidyl ether) (P(HZ‐co‐BnGE)), is synthesized via thiol‐ene click reaction of poly(allyl glycidyl ether‐co‐benzyl glycidyl ether) (P(AGE‐co‐BnGE)). The base polymer P(AGE‐co‐BnGE) is previously prepared by anionic ring‐opening copolymerization of the corresponding monomers. To demonstrate utility, bicompartmental microspheres and microcylinders containing P(HZ‐co‐BnGE) in one of the compartments are prepared via electrohydrodynamic (EHD) co‐jetting. Next, spatially controlled surface reactivity toward sugars is demonstrated by selective binding of 2α‐mannobiose to the P(HZ‐co‐BnGE) compartment only, as confirmed by a carbohydrate‐lectin‐binding assay. These sugar‐reactive hydrazide‐presenting microparticles have potential applications for glyco‐targeted drug delivery. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>